Endotoxin Activity in Neonates Undergoing Cardiac Surgery: Cohort Study. Issue 1 (January 2018) - Ricci, Zaccaria; Benegni, Simona; Garisto, Cristiana; Favia, Isabella; Haiberger, Roberta; Di Chiara, Luca
Background: Endotoxemia in pediatric cardiac surgical patients is poorly understood. The endotoxin activity assay (EAA) levels were examined in neonates undergoing cardiac surgery in order to assess their reference levels and their association with other pre-, intra-, and postoperative risk factors for gut hypoperfusion. We finally observed if refeeding was associated with modification of endotoxin levels. Methods: In a prospective cohort study, neonates undergoing surgery for correction or palliation were enrolled. Preterm birth, weight below 1.5 kg, the need for extracorporeal membrane oxygenation, and urgent surgery were exclusion criteria. Results: Among the 26 enrolled neonates, 12 underwent on-pump and 14 off-pump surgery, 22 received a preoperative infusion of prostaglandin E2. Overall, 11 patients were surgically corrected and 15 received a palliation. Endotoxin activity assay baseline levels were inversely correlated with age at surgery ( r = −.50, P = .006) and they increased to postoperative day2 ( P = .002). On-pump versus off-pump surgery ( P =.36) and surgical palliation with a Blalock-Taussig shunt versus correction ( P = .45) did not predict increase in EAA levels. Aortic clamping for coarctation repair was associated with the lowest levels ( P = .04). Systolic, mean, and diastolic pressures were associated with EAA levels ( r = −.55, P = .01; r = −.45, P = .02; r = −.37, P = .04, respectively). Endotoxin activity assay levels after refeeding were similar to baseline levels. Patients with abdominal distension and feeding intolerance showed higher median peak EAA levels (0.7, 0.66-1.11) than asymptomatic patients (0.53, 0.35-0.64; P = .01). Conclusions: Endotoxin activity assay levels increase after elective neonatal surgery and are not modified by refeeding. High postoperative levels may predict feeding intolerance.